The pluriverse of disasters: knowledge, mediation and citizenship - Parmar, C (2012)
This thesis looks at a variety of stakeholders and how they inform the conversations around disasters and disaster sites. In particular it focuses on the way knowledge frameworks of different actors informs this dialogue and defines the nature of their response. The thesis argues that this has an implication for debates on democracy, governance and citizenship. The thesis looks at four sets of actors: individuals confronting and coping with the everydayness of disasters.; the states of Gujarat and Orissa in India which innovate in the face of disasters to either create a techno-managerial response and institute different methodologies or use the existing structures to embed themselves further and perpetuate the poverty and disaster industry; the Christian and secular humanitarian groups: the former make a transition from charity to rights discourse while intervening in disasters. The latter focus on building methodologies which institute certain norms of responding to disasters and catering to those it considers as more vulnerable when disaster strikes. The thesis finally turns its attention to the response of four Hindu groups who draw on civilizational categories to engage with issues of pain, suffering, healing. Each stakeholder, the thesis argues, in articulating its response to disasters, presents a 'counter model' or at least a complementary understanding of how to think and respond to disasters. This plurality of engagement by questioning the preconceived frameworks adds not just to the democratic imagination but also to the debates on what constitutes governance and citizenship. Methodologically, the thesis is an ethnographic exploration located in two sites in India: Gujarat and Orissa. It keeps storytelling, ethnography, analysis, policy documents together and tries to show that they become a weave in disaster studies.